Fora da ordem: Foucault e a exclusão na idade clássica - Martins, Cláudia Maria (2012)
The purpose of our thesis was to reconstruct fundamental aspects of Michel Foucault's philosophy from a problematic cell inscribed within Histoire de la Folie à l'âge classique. It concerns the thesis which claims that the impossibility of being mad is the first qualification acquired by the Cartesian subject, even before Cogito statement. Foucault's polemical stance gives raise to the episode known by the Foucault-Derrida dispute. In the text Mon corps, ce papier, ce feu , written in 1972, Foucault explicits such reading by identifying in Descartes's Meditations a double weft: a demonstrative discourse guided by the order of reasons and an ascetic discourse guided by the performatic exercise of creating the subject of knowledge. The present research has showed that, in such a rare moment when Foucault puts himself in the role of a commentator of a philosophical text, the highlighted aspects in the Cartesian text are equally emblematic of his own philosophical method. Characterized by pointing out the visible and the enunciable, Foucault's histories also make up a double weft and encourage a kind of ascesis